Differences Of COVID-19 Antibody Titer In The Group After The Two Sinovac Vaccine And The Three Moderna Of Prodia Employees Yogyakarta - Elisabeth Yann Tri Undari; Hari Saktiningsih (POLTEKKES KEMENKES YOGYAKARTA, 2023)
This study compared antibody levels in individuals after receiving the second dose of the Sinovac vaccine and the third dose of the Moderna vaccine. Sinovac, developed in China, uses the inactivated virus method, meaning it contains no live virus. In contrast, the Moderna vaccine, created in the United States, is an mRNA vaccine that prompts the immune system to produce spike proteins, leading to antibody production without using a live virus. Conducted on Prodia employees in Yogyakarta, this observational research used a cross-sectional approach to measure antibody titers after vaccination. The results, analyzed using the Wilcoxon signed test, showed a significant difference in COVID-19 antibody levels between the two groups.